(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Nonalcoholic steatohepatitis (NASH) and advanced fibrosis are the spectrum of nonalcoholic fatty liver disease (NAFLD) that may progress to cirrhosis. Objective: We aimed to determine the detecting capacity of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and gamma glutamyl transpeptidase (GGT) for NASH and significant fibrosis. Methods: Demographic and laboratory data of 502 sonologically diagnosed NAFLD patients were retrospectively analysed. Area under receiver operating characteristics curve (AUROC) was performed for NASH and fibrosis score ?2 (significant fibrosis) with ALT, AST and GGT of 233 biopsied patients. Results: Of 502 patients ALT, AST and GGT was elevated in 252 (50.1 %), 184 (36.7%) and 138 (27.4%) respectively. There was no difference in histological activity and fibrosis score between normal and elevated ALT and AST. Forty two (40.2%) NASH and 23(20.2%) significant fibrosis had normal ALT level. GGT was differed in NASH and Non NASH (p< .005) and between significant fibrosis (p< .01) and insignificant fbrosis. To detect NASH AUROC curve ofGGT was 67.5%, whereas of ALT and AST was 55.2% and 55.7%. For significant fibrosis AUROC curve of ALT, AST and GGT was 44, 50 and 68.4 % respectively. GGT level of39.5 U/L could detect NASH with a 63% sensitivity and 65% specificity irrespective of sex. GGT 40.5U/L had 60% sensitivity and 59 % specificity to detect significant fibrosis. For fibrosis ?2 AUROC curve was 75.4% in male. Conclusion: No optimal ALT and AST level could detect NASH and fibrosis. GGT level of 40 U/L had a better detecting capacity for NASH and fibrosis especially in male.